2001
DOI: 10.1203/00006450-200104000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Innate Immune Response in the Immature Human Intestine: Toll-Like Receptors on Fetal Enterocytes

Abstract: The intestinal epithelium is an active participant in the mucosal immune response against luminal pathogens. Microorganisms and their cell wall products, i.e. lipopolysaccharide (LPS), can stimulate the enterocyte to produce an innate immune response with the increased production of IL-8 via an activation of the transcription factor NFB. The innate response mechanism, however, has not been understood until the recent description of a family of human toll-like receptors (hTLR) on immune cells that interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 18 publications
4
124
1
Order By: Relevance
“…We and others have previously demonstrated that IEC express very low levels of TLR4 and its coreceptor MD-2 and are unresponsive to LPS (73,83,89). Recent studies demonstrate that intestinal macrophages are also poorly LPS responsive and lack CD14 (90).…”
Section: Discussionmentioning
confidence: 92%
“…We and others have previously demonstrated that IEC express very low levels of TLR4 and its coreceptor MD-2 and are unresponsive to LPS (73,83,89). Recent studies demonstrate that intestinal macrophages are also poorly LPS responsive and lack CD14 (90).…”
Section: Discussionmentioning
confidence: 92%
“…We reasoned that, due to the expression of TLR4 and TLR2 by fetal enterocytes and the latter's hypersensitivity to LPS (36,37) as well as the high levels of sCD14 in milk (16,17), the milk sCD14-mediated microbial recognition in the neonatal gut must be regulated to avoid excessive local inflammation.…”
Section: Detection Of Stlr2 Polypeptides In Human Breast Milkmentioning
confidence: 99%
“…A large body of data suggests that imbalance between Toll like receptors 4 (TLR) and TLR 9 is responsible for development of the disease. TLR4 activation leads to apoptosis and effects enterocyte proliferation and migration [21]. Some studies have implicated the role of Paneth cells (PCs) in NEC.…”
Section: Pathogenesismentioning
confidence: 99%